Studies on Applicability of Poly electrolyte Complex of Vancomycin Hydrochloride for Colon Targeting Beads Using Statistical Optimization - Venkateshwarlu, K. (Asian Journal of Pharmaceutics (AJP), 2019)
The present study was initiated to develop colon targeted enteric coated hard capsule containing chitosan-based polyelectrolyte complex (PEC) beads of vancomycin HCl 500 mg. The chitosan-based PEC beads were development and optimized using 32-full factorial design based on two independent factors were evaluated, each at three levels for all nine possible combinations. The PEC beads were prepared by an ionic gelation method using positively charged chitosan and negatively charged hupu gum. The vancomycin HCl is an orally administered amphoteric glycol peptides, an antimicrobial substance used in the treatment of enterocolitis caused by Staphylococcus aureus and antibioticassociated with pseudomembrane colitis caused by Clostridium difficile. Hence, localization of the drug at its site of action is more useful. The pharmacokinetic parameters of the drug also offer feasibility for colon-specific drug delivery and were developed with a view to have lag time 4–6 h, controlled release in the colon over a period of 16–20 h. The final optimized formulation is further subjected to enteric coating using Eudragit-S100 and subjected to in vitro studies. The optimized formulation showed ˂12% drug release during lag time, 91.34% at 20 h. The study was carried out to check the ability of PEC beads to release the vancomycin HCl in the presence of rat cecal content medium resembling the physiological environment of colon. The results for this ex vivo revealed that optimized formulations are susceptible to colonic enzymes released from rat cecal contents. The significance of differences was evaluated by analysis of variance.